ISF-1: First high oleic safflower variety developed in India - Kammili, Anjani; Yadav, Praduman; Reddy, A Vishnuvadhan (Indian Farming, 2020)
Safflower (Carthamus tinctorius L.) is a multipurpose oilseed crop with worldwide adaptability. India is one of the top safflower growing countries. Demand for high oleic safflower oil is increasing globally. However, Indian safflower cultivars possess very low oleic acid content (14- 19%) in oil. In view of the high industrial demand for high oleic safflower oil, the first high oleic safflower variety, ISF-1 was developed at ICAR-IIOR, Hyderabad. ISF-1 has consistently exhibited high oleic acid content (73-80.8%) across India under both wet and dry conditions, as well under hot and cool climates over years. ISF-1 gave on average 3.6 q/ha oleic acid yield under rainfed and 4.9 q/ha under irrigated conditions while the leading safflower variety, PBNS-12 gave 0.86 q/ha under rainfed and 1.1 q/ha under irrigated conditions. ISF-1 has recorded seed and oil yield at par with PBNS-12 in farmers’ fields under both rainfed and irrigated conditions.